High‐Pressure Sintering of Rhombohedral Cr2S3 Using Titanium–Zirconium–Molybdenum Tools. Issue 11 (1st September 2019) - Groeneveld, Dennis; Groß, Hendrik; Hansen, Anna-Lena; Dankwort, Torben; Hansen, Julian; Wöllenstein, Jürgen; Bensch, Wolfgang; Kienle, Lorenz; König, Jan
Abstract : The influence of sintering parameters on the physical properties and the chemical structure of rhombohedral Cr2 S3 (rh‐Cr2 S3 ) is investigated using high pressures and high temperatures. The densification of the powder is performed by applying the high‐pressure field‐assisted sintering technique/spark plasma sintering. Using a titanium–zirconium–molybdenum (TZM) alloy as sintering tool, it is possible to increase the magnitude of the applied pressure to several hundred MPa at temperatures as high as 1223 K. A relative density of up to 99.9% is achieved at a sintering temperature of 1223 K and a pressure of 395 MPa. The presence of phase‐pure rh‐Cr2 S3 is proven by X‐ray diffraction analysis and transmission electron microscopy. The Seebeck coefficients of the self‐doped samples change drastically with the sintering temperatures ranging between −650 and −350 μV K −1 . The densities and the thermal conductivities of the sintered samples increase with increasing sintering temperatures. The electrical conductivity is largely increased compared with the thermal conductivity potentially due to the current‐assisted high‐pressure sintering. Abstract : Highly densified rhombohedral Cr2 S3 is successfully prepared by high‐pressure field‐assisted sintering technique using titanium–zirconium–molybdenum alloy sintering tools. A theoretical density of 99.9% is achieved by sintering at 1223 K and 395 MPa. The investigation of the microstructure proves that the initial structure is preserved. The electrical and the thermal conductivities indicate a strong dependency of the microstructure.